Biological effects of pyropheophorbide-a as photosensitizer and prooxidant - MA Shi-cheng; YU Hai-ning; SHEN Sheng-rong (浙江大学学报. 农业与生命科学版)
UV-visible absorption, chemiluminescence and ESR (electron spin-resonance) were employed to investigate characteristics of pyropheophorbide-a. The results showed that pyropheophorbide-a was photosensitized and prooxidated as the way of model Ⅱ; By estimating the viability of Tn-5B1-4 cells and mortality of third instar larvae of Plutella xylostella L. under illumination, it was found that pyropheophorbide-a significantly influenced on the viability of Tn-5B1-4 cells and the mortality of third instar larvae of P. xylostella L. The cell viability of Tn-5B1-4 was reduced to 6.29%, disposed with pyropheophorbide-a for 48 h with 30 min light irradiation at the concentration of 10 μmol·L-1. After fed with pyropheophorbide-a 48 h with irradiation of ultraviolet and sunlight for 1 h, the death rate of third instar larvae of P. xylostella L., was 60% and 100%, respectively, significantly different with control. It was indicated that pyropheophorbide-a is an excellent photosensitizer and prooxidant in biological applications.